2017
DOI: 10.1051/0004-6361/201731391
|View full text |Cite
|
Sign up to set email alerts
|

Molecular gas in theHerschel-selected strongly lensed submillimeter galaxies atz ~ 2–4 as probed by multi-JCO lines

Abstract: We present the IRAM-30 m observations of multiple-J CO (J up mostly from 3 up to 8) and [C I]( 3 P 2 → 3 P 1 ) ([C I](2-1) hereafter) line emission in a sample of redshift ∼ 2-4 submillimeter galaxies (SMGs). These SMGs are selected among the brightest-lensed galaxies discovered in the Herschel-Astrophysical Terahertz Large Area Survey (H-ATLAS). Forty-seven CO lines and 7 [C I](2-1) lines have been detected in 15 lensed SMGs. A non-negligible effect of differential lensing is found for the CO emission lines, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

36
228
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(266 citation statements)
references
References 298 publications
(513 reference statements)
36
228
2
Order By: Relevance
“…Figure 13 displays the relation between the apparent CO luminosities, L ′ CO(1−0) , and the width (∆V) of the CO emission lines for the sources presented in this work and a compilation of high-z lensed and unlensed SMGs, as well as local ULIRGs from the literature (see figure caption for details and references). This relationship has already been presented and discussed in previous studies (e.g., Harris et al 2012;Bothwell et al 2013;Carilli & Walter 2013;Aravena et al 2016;Yang et al 2017;Dannerbauer et al 2017;Isbell et al 2018). Figure 13 includes CO measurements of ∼160 galaxies in total; it should be noted that none of the gravitationally lensed sources in this plot was corrected for lensing magnification.…”
Section: Co Luminosities and The L ′supporting
confidence: 75%
“…Figure 13 displays the relation between the apparent CO luminosities, L ′ CO(1−0) , and the width (∆V) of the CO emission lines for the sources presented in this work and a compilation of high-z lensed and unlensed SMGs, as well as local ULIRGs from the literature (see figure caption for details and references). This relationship has already been presented and discussed in previous studies (e.g., Harris et al 2012;Bothwell et al 2013;Carilli & Walter 2013;Aravena et al 2016;Yang et al 2017;Dannerbauer et al 2017;Isbell et al 2018). Figure 13 includes CO measurements of ∼160 galaxies in total; it should be noted that none of the gravitationally lensed sources in this plot was corrected for lensing magnification.…”
Section: Co Luminosities and The L ′supporting
confidence: 75%
“…The global source-plane CO SLED in SDP.81 peaks between Jupp = 5 and 9 (in units of L ), with a sharp drop at Jupp = 10 ( Fig. 8, see also Yang et al 2017, for a recent sky-plane analysis). Compared to the Rosenberg et al (2015) study of CO excitation in present-day ULIRGS, the sharp drop in LCO for Jupp ≥ 9 and minor CO contribution to the global neutral gas cooling makes SDP.81 akin to Rosenberg et al (2015) Class I sources, which have similarly low CO cooling contributions (≤ 10 per cent).…”
Section: Co Spectral Energy Distributionmentioning
confidence: 93%
“…By including only Jupp ≥ 3 CO lines (critical density ncrit ≥ 8 × 10 3 cm −3 , we effectively discount the extended cold, low-density (n ≤ 10 3 cm −3 ) gas phase traced by CO(1-0) and CO(2-1) lines. Indeed, studies of the CO ladders including the Jupp = 1 − 2 lines have found significant cold gas components both in z ∼ 0 ULIRGs (e.g., Kamenetzky et al 2014;Greve et al 2014) and high-redshift DSFGs (e.g., Bothwell et al 2013;Yang et al 2017). While the cold gas component can contribute to the CO(3-2) and CO(5-4) luminosity, the Yang et al (2017) source-averaged CO SLED model for SDP.81 -which includes both a cold and a warm component -shows the cold-gas contribution to the CO(3-2) and CO(5-4) luminosities to be ≤30 and <10 per cent, respectively.…”
Section: Caveats and Limitationsmentioning
confidence: 99%
“…We also compare the CO SLED of J2310+1855 with high redshift systems, including high redshift (lensed) SMGs and quasars. Figure 6 (a) shows the CO SLED of J2310+1855 and high redshift SMGs: a sample of z ∼ 1.2 − 4.1 SMGs (Bothwell et al 2013) and a sample of 15 z ∼ 2 − 4 lensed SMGs from Carilli & Walter (2013) and Yang et al (2017). The high redshift SMG CO SLEDs peak at J 6, while J2310+1855 peaks at higher J (J = 8) than the two SMG samples.…”
Section: The Co Emission In J2310+1855 Compared With High Redshift Symentioning
confidence: 99%
“…Recent studies found a nearly linear relation between the water luminosity and the infrared luminosity in local and high redshift systems over three orders of magnitude (González-Alfonso et al 2010;? ;Riechers et al 2013;Yang et al , 2017Omont et al 2013;Jarugula et al 2019). The brightest water lines are detected in the presence of shocks or X-rays (González-Alfonso et al 2010;Pellegrini et al 2013).…”
mentioning
confidence: 99%